Fibromatosis-like metaplastic carcinoma: a case report and review of the literature - Jasper Victoor; Claire Bourgain; Sara Vander Borght; Isabelle Vanden Bempt; Carine De Rop; Giuseppe Floris (BMC, 2020)
Abstract Background We report an unusual case of low-grade fibromatosis-like metaplastic carcinoma (LG-FLMC) of the breast. This exceedingly rare epithelial breast malignancy has been reported only 68 times in the past 20 years, and is classified as a subtype of metaplastic breast carcinoma (MBC). It is a locally aggressive tumor with a low potential for lymph node and distant metastases, but with a tendency to recur after excision. Here we describe a less common presentation of LG-FLMC, provide its molecular characterization, discuss the major differential diagnosis and bring a short review of the literature. Case presentation A 65-year-old woman presented with a self-palpated breast lump that had discordant radio-pathological features. While imaging results were compatible with an infiltrative malignancy, on core needle biopsy (CNB) a sharply delineated lesion composed by a bland-looking population of spindle cells was observed; excision was recommended for final diagnosis. Histology of the resection specimen showed small areas of epithelial differentiation and foci of peripheral invasion. Immunohistochemical analysis revealed a co-immunoreactivity for epithelial and myoepithelial markers in the spindle cell component. Mutation analysis with a capture-based next generation sequencing method revealed pathogenic mutations in GNAS, TERT-promotor and PIK3R1 genes. A diagnosis of LG-FLMC was rendered. Conclusion This case highlights the importance of a broad differential diagnosis, exhaustive sampling and the use of a broad immunohistochemical panel whenever dealing with a low-grade spindle cell lesion in the breast, and provides further insights into the molecular background of LG-FLMC.